LITHO-MAGNETIC AND STRUCTURAL MAPPING FROM INTERPRETATION OF HIGH RESOLUTION AEROMAGNETIC DATA OVER NORTHERN BIDA BASIN AND ENVIRONS NORTH-CENTRAL NIGERIA - Barka, Jonathan; Yusuf, Abubakar; Ezekiel, Kamureyina (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
Recently, the Nigerian Geological Survey Agency (NGSA) acquired high resolution airborne data over Nigeria and have commenced surface geological mapping in some parts of the country. This research becomes imperative taking into account time consumption and the risk associated with geological field mapping in recent time which includes difficulty in terrain coverage, abduction of field workers and insurgency in some part of the country. In this research an attempt was made to carry out litho-magnetic mapping and delineation of surface structures from interpretation of high resolution aeromagnetic data within northern Bida basin and environs. High resolution aeromagnetic data of the study area was subjected to regional residual separation, analytical signal, vertical derivative, tilt angle derivative, horizontal tilt derivative and upward continuation filters in the Oasis Montaj Version 7.0.1 Geo-software environment to enhance data for interpretation. Results from the total magnetic intensity (TMI) and residual data shows that magnetic intensity values range from 33,961.54 nT to 34,124.84 nT and -37.75nT/m to 124.08 nT/m respectively. Results of litho-magnetic mapping on the basis of magnetic susceptibilities helped in demarcating lithologies associated with Basement Complex and sedimentary terrains. Structures mapped in the study area are faults which trends in the NE-SW and NW-SE dominant directions and other minor direction are in the E-W. These results put together assisted in the preparation of a comprehensive litho-magnetic and structural map of the study area.